A knock‐in mouse model for KCNQ2‐related epileptic encephalopathy displays spontaneous generalized seizures and cognitive impairment. (2nd April 2020) - Milh, Mathieu; Roubertoux, Pierre; Biba, Najoua; Chavany, Julie; Spiga Ghata, Adeline; Fulachier, Camille; Collins, Stephan Christopher; Wagner, Christel; Roux, Jean‐Christophe; Yalcin, Binnaz; Félix, Marie‐Solenne; Molinari, Florence; et al.
Abstract: Objective: Early onset epileptic encephalopathy with suppression‐burst is one of the most severe epilepsy phenotypes in human patients. A significant proportion of cases have a genetic origin, and the most frequently mutated gene is KCNQ2, encoding Kv7.2, a voltage‐dependent potassium channel subunit, leading to so‐called KCNQ2 ‐related epileptic encephalopathy ( KCNQ2 ‐REE). To study the pathophysiology of KCNQ2 ‐REE in detail and to provide a relevant preclinical model, we generated and described a knock‐in mouse model carrying the recurrent p.(Thr274Met) variant. Methods: We introduced the p.(Thr274Met) variant by homologous recombination in embryonic stem cells, injected into C57Bl/6N blastocysts and implanted in pseudopregnant mice. Mice were then bred with 129Sv Cre‐deleter to generate heterozygous mice carrying the p.(Thr274Met), and animals were maintained on the 129Sv genetic background. We studied the development of this new model and performed in vivo electroencephalographic (EEG) recordings, neuroanatomical studies at different time points, and multiple behavioral tests. Results: The Kcnq2 Thr274Met/+ mice are viable and display generalized spontaneous seizures first observed between postnatal day 20 (P20) and P30. In vivo EEG recordings show that the paroxysmal events observed macroscopically are epileptic seizures. The brain of the Kcnq2 Thr274Met/+ animals does not display major structural defects, similar to humans, and their body weight is normal. Kcnq2 Thr274Met/+ mice have a reduced life span, with a peak of unexpected death occurring for 25% of the animals by 3 months of age. Epileptic seizures were generally not observed when animals grew older. Behavioral characterization reveals important deficits in spatial learning and memory in adults but no gross abnormality during early neurosensory development. Significance: Taken together, our results indicate that we have generated a relevant model to study the pathophysiology of KCNQ2 ‐related epileptic encephalopathy and perform preclinical research for that devastating and currently intractable disease.